Graphene oxide / silk fibroin nanofiber drug-loaded multilayer film as well as preparation method and application thereof
Through layer-by-layer self-assembly technology, graphene oxide/silicon nanofiber multilayer membrane is formed, and anti-cancer drugs are loaded through physical adsorption, which solves the problem of insufficient drug-loading and drug release performance in the prior art, and achieves rapid release and high drug loading, which is suitable for cancer treatment.
Patent Information
- Application Number
- CN202411913552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
It is difficult to develop a multilayer membrane with excellent drug-loading and drug-release properties for cancer treatment.
Through layer-by-layer self-assembly technology, graphene oxide and silk fibroin nanofibers are used to form a multi-layer film, and anti-cancer drugs such as doxorubicin are loaded through physical adsorption methods to form a graphene oxide/silicon nanofiber drug-loaded multi-layer film.
The rapid drug release and high drug loading of multi-layer membranes can effectively increase the concentration of drugs in tumor tissues and reduce damage to normal tissues. The preparation method is simple and easy to implement, and is suitable for large-scale production.
Smart Images

Figure CN119700719A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a graphene oxide / silk fibroin nanofiber drug-carrying multilayer film and a preparation method and application thereof. Background Art
[0002] In today's world, malignant tumors have become a huge challenge, posing a threat not only to the physical health of patients, but also to the entire society. In recent years, researchers have been committed to developing more effective drug delivery systems for cancer treatment, with the goal of ensuring excellent efficacy while reducing side effects. With the maturity of nanotechnology, the advantages of nano drug delivery systems have gradually emerged. The system has high selectivity for tumors and can slowly release active anticancer agents. A promising approach is to develop drug delivery systems that can accurately target tumor cells and control drug release. Among them, layer-by-layer self-assembly technology is widely used in the surface modification of biomedical materials due to its advantages such as flexible base plate, simple operation, wide application, and controllable thickness. Layer-by-layer self-assembly is a technology that spontaneously forms thin films by alternating deposition processes driven by weak interaction forces between chemical groups on the template surface and film-forming substances. This flexibility greatly expands the application range of layer-by-layer self-assembled multilayer films, especially in the field of medical materials, where its ability to construct composite functional films and drug carriers is widely recognized.
[0003] However, how to provide a multilayer film for drug loading with excellent drug loading and drug release performance is a difficult problem in the prior art. Summary of the invention
[0004] The object of the present invention is to provide a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film and a preparation method and application thereof, so as to simultaneously meet the excellent drug loading and drug release properties of the multilayer film.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] The present invention provides a method for preparing a graphene oxide / silk fibroin nanofiber multilayer film, comprising the following steps:
[0007] S1, immersing the substrate in a graphene oxide (GO) solution for 10-15 min, and then washing it three times with deionized water;
[0008] S2, immersing the substrate obtained in step S1 in a silk fibroin nanofiber (SNF) solution for 10-20 min, and then washing it three times with deionized water to form a GO / SNF double-layer membrane on the substrate;
[0009] S3, repeating the immersion and cleaning operations in steps S1 and S2 on the substrate containing the GO / SNF double-layer film obtained in S2 to form a (GO / SNF)n multilayer film on the substrate, wherein n represents the number of GO / SNF layers;
[0010] S4. The (GO / SNF)n multilayer film obtained in S3 is cross-linked to form a cross-linked (GO / SNF)n multilayer film on the substrate, that is, a graphene oxide / silk fibroin nanofiber multilayer film.
[0011] In one embodiment of the present invention, in step S1, the substrate is selected from a silicon wafer or a glass slide.
[0012] In one embodiment of the present invention, in step S1, before immersing the substrate in the graphene oxide (GO) solution, the substrate is cleaned using a plasma cleaning apparatus so that the substrate is negatively charged.
[0013] In one embodiment of the present invention, in step S1, the concentration of the graphene oxide solution is 1.0-1.5 mg / mL.
[0014] In one embodiment of the present invention, in step S2, the concentration of the silk fibroin nanofiber (SNF) solution is 1.0-1.5 mg / mL.
[0015] In one embodiment of the present invention, in step S2, the silk fibroin nanofiber (SNF) is prepared by the following method:
[0016] A1. Put the chopped silk cocoons into a degumming solution and boil for 30-60 minutes, wash three times, and dry to obtain degummed silk;
[0017] A2, dissolving the degummed silk in a sodium hydroxide / urea mixed solution, freezing for 12-24 hours, stirring for 15-30 minutes, repeating the operation 3-5 times to obtain a silk fibroin fiber solution;
[0018] A3. Put the silk fibroin fiber solution into a dialysis bag, place it in deionized water, and dialyze it for 2-3 days. After dialyzed, subject the solution to ultrasonic centrifugation, take the supernatant and pre-cool it at -20℃~-25℃ for 24h, then place it in a freeze dryer for freeze drying for 36-48h to obtain white powder silk fibroin nanofiber (SNF), which is stored in a 4℃ refrigerator for later use.
[0019] In one embodiment of the present invention, in step A1, the degumming solution is a 0.4-0.6% (w / v) sodium carbonate or sodium bicarbonate aqueous solution.
[0020] In one embodiment of the present invention, in step A2, in the sodium hydroxide / urea mixed solution, the mass ratio of sodium hydroxide to urea is 1.0-1.5:1.
[0021] In one embodiment of the present invention, in step S4, the method for performing the cross-linking treatment is:
[0022] The substrate formed with the (GO / SNF)n multilayer film structure is immersed in a 0.05-0.06 mol / L morpholineethanesulfonic acid (MES) solution containing 0.2-0.3 mol / L 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 5.0-6.0 mmol / L N-hydroxysuccinimide (NHS) for 20-30 min, and then cross-linked in a 2.5% glutaraldehyde solution for 30-60 min, and rinsed three times with deionized water to form a cross-linked (GO / SNF)n multilayer film on the substrate, that is, a graphene oxide / silk fibroin nanofiber multilayer film.
[0023] The present invention further provides a graphene oxide / silk fibroin nanofiber multilayer film prepared based on the above method. The graphene oxide / silk fibroin nanofiber multilayer film is attached to a substrate and can be used for drug loading, and the graphene oxide / silk fibroin nanofiber multilayer film can also be peeled off from the substrate for other uses.
[0024] The graphene oxide / silk fibroin nanofiber multilayer membrane provided by the present invention is formed by layer-by-layer self-assembly membrane technology using amino-modified graphene oxide GO-NH2 and silk fibroin nanofibers as main materials.
[0025] The present invention further provides the use of the graphene oxide / silk fibroin nanofiber multilayer membrane prepared based on the above method, wherein the graphene oxide / silk fibroin nanofiber multilayer membrane is used for drug loading to prepare the graphene oxide / silk fibroin nanofiber drug-loaded multilayer membrane.
[0026] The present invention further provides a method for preparing a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film, comprising the following steps:
[0027] The substrate formed with the graphene oxide / silk fibroin nanofiber multilayer film is immersed in a drug solution for 1.0-1.5 hours, and then the multilayer film is cleaned to remove the unloaded drug, thereby obtaining the graphene oxide / silk fibroin nanofiber drug-loaded multilayer film. The graphene oxide / silk fibroin nanofiber drug-loaded multilayer film is attached to the substrate, and the graphene oxide / silk fibroin nanofiber drug-loaded multilayer film can be peeled off from the substrate.
[0028] In one embodiment of the present invention, the concentration of the drug solution is 1.0-1.5 mg / mL.
[0029] In one embodiment of the present invention, the drug is doxorubicin for anti-tumor. At this time, the concentration of the doxorubicin (DOX) drug solution is 1.0-1.5 mg / mL.
[0030] The present invention further provides a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film prepared based on the above method.
[0031] The present invention further provides the use of the graphene oxide / silk fibroin nanofiber drug-loaded multilayer film prepared based on the above method in the preparation of drugs or drug carriers with precisely controlled drug release.
[0032] Graphene oxide (GO) is a derivative of graphene. It has a lamellar structure and contains a large number of oxygen-containing functional groups, showing unique optical, thermal and mechanical properties. Aminated graphene oxide is a product obtained by functionalizing graphene oxide. Its structure is similar to that of graphene oxide, but with amino functional groups attached to the surface. Amino functional groups are usually introduced onto the surface of graphene oxide by reaction with an amination reagent (such as ammonia gas or ammonia water). The introduction of amino functional groups gives graphene oxide new chemical activity and properties.
[0033] Silk fibroin material is extracted from natural silk, and its structure consists of two parts: crystalline region and non-crystalline region. The crystalline region is composed of amino acid residues, of which the molar ratio of glycine, alanine and serine is 4:3:1, accounting for 85% in total, and arranged into relatively regular segments according to a certain sequence. In contrast, phenylalanine, tyrosine, tryptophan and other amino acids with larger side chains are mainly distributed in the non-crystalline region. Due to its unique biocompatibility, biodegradability and controlled release potential for bioactive molecules. By encapsulating drugs in silk fibroin coatings, local treatment of tumors can be achieved, reducing toxic side effects to the entire body. Traditional tumor treatment methods often face some challenges, such as drug toxicity, multidrug resistance and poor treatment effects. Using silk fibroin as a drug carrier can achieve local release and targeted delivery of drugs, thereby reducing the concentration and dosage of drugs in the body, reducing adverse reactions and improving treatment effects.
[0034] The present invention utilizes the self-assembly characteristics of silk fibroin and graphene oxide materials, and by utilizing layer-by-layer self-assembly technology, creates a complex graphene oxide / silk fibroin nanofiber multilayer film, which can encapsulate anti-tumor drugs and achieve targeted delivery to cancer tissues. Based on this technology, tumor targeting ligands or functional groups are modified on the surface of the graphene oxide / silk fibroin nanofiber multilayer film to achieve local treatment of tumors. This local treatment strategy can effectively increase the concentration of drugs in tumor tissues and reduce damage to normal tissues.
[0035] The present application scheme uses layer-by-layer self-assembly technology to prepare a graphene oxide / silk fibroin nanofiber (GO / SNF) multilayer membrane with electrostatic interaction as the driving force, and then uses a physical adsorption method to load commonly used anticancer drugs such as doxorubicin (DOX) into the multilayer membrane, thereby obtaining a (DOX-GO / SNF) multilayer membrane containing doxorubicin anti-tumor drugs.
[0036] Specifically, the present application treats the bottom silicon wafer with plasma to make it negatively charged, and then immerses it in a positively charged polyelectrolyte solution for coating deposition, such as amino-modified graphene oxide GO-NH2. After washing with deionized water, it is further immersed in a negatively charged polyelectrolyte solution for coating deposition, such as a silk protein nano solution. After repeating multiple cycles, after obtaining a layer-by-layer self-assembled multilayer film coating, chemical cross-linking is performed, and then the coated silicon wafer is immersed in a certain concentration of doxorubicin solution for drug loading, and after washing, a coating (multilayer film) containing doxorubicin anti-tumor drugs is obtained.
[0037] This application also studies the micromorphology and in vitro drug release behavior of the drug-loaded multilayer membrane. The test results show that the surface of the graphene oxide / silk fibroin nanofiber (GO / SNF) multilayer membrane has a microporous structure, and its drug loading can be controlled by adjusting the number of membrane layers. This local treatment strategy can effectively increase the concentration of drugs in tumor tissues and reduce damage to normal tissues. This application also analyzes the loading and release characteristics of the drug in PBS buffer that simulates the osmotic pressure and temperature of the human body. The background of this study highlights the importance of exploring innovative cancer treatment strategies, especially the use of advanced materials and manufacturing technologies to enhance therapeutic effects.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The present invention discloses that GO and SNF are used as raw materials, and a GO / SNF multilayer film is deposited on the surface of a silicon wafer by a layer-by-layer self-assembly film forming technology with electrostatic interaction as a driving force, and then an anticancer drug-doxorubicin (DOX) is loaded to obtain a DOX-GO / SNF multilayer film.
[0040] (2) The multilayer film was characterized by using UV-vis and SEM, revealing that the growth and formation process of the multilayer film is uniform, the surface of the film is rough and has a rich porous structure. In the study of the simulated drug release behavior of the drug-loaded multilayer film in vitro, the present invention found that the multilayer film has rapid drug release. The drug loading amount of the multilayer film is positively correlated with the number of layers of the multilayer film, and its drug loading amount can be regulated by controlling the number of layers of the multilayer film. The preparation method of the membrane is simple and easy, which meets the requirements of large-scale batch production. The performance of the membrane is easy to control. Through subsequent optimization design, its encapsulation of anti-tumor drugs and anti-cancer drug loading performance is expected to be further improved, thereby enabling targeted delivery to cancer tissues. Tumor targeting ligands or functional groups are modified on its surface to achieve local treatment of tumors. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is the extraction flow chart of SNR suspension;
[0042] Figure 2 Schematic diagram of the preparation of DOX-GO / SNF drug-loaded multilayer film;
[0043] Figure 3 SEM images of (SNR)10, (GO / SNR)10, and (GO / SNR)20 multilayer films;
[0044] Figure 4 Schematic diagram of (GO / SNR)n multilayer film loading DOX drug;
[0045] Figure 5 is the drug loading content of different film thicknesses (GO / SNR)n (n=5, 10, 15, 20);
[0046] Figure 6 DOX-(SNR) 10 、DOX-(GO / SNR) 10 and DOX-(GO / SF) 20 Drug release profiles of multilayer films;
[0047] Figure 7 DOX-(SNR) 10 、DOX-(GO / SNR) 10 and DOX-(GO / SF) 20 SEM images of the multilayer films before and after drug release. DETAILED DESCRIPTION
[0048] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] Example 1
[0050] Preparation of silk fibroin nanofibers SNR, reference Figure 1 , the steps are:
[0051] A1. After the silk cocoons are cut into pieces, they are placed in a 0.5% (w / v) sodium carbonate solution and boiled for 30 minutes for degumming, and then fully washed with deionized water. This process is repeated twice. The residual sericin and Na2CO3 are washed away with ultrapure water and then dried to obtain degummed silk (DS).
[0052] A2, prepare 100g sodium hydroxide / urea solution (sodium hydroxide:urea mass ratio = 1.38:1), and precool at -20°C;
[0053] A3. Take 4 g of DS and add it to the pre-cooled solution, freeze it at -20°C for 12 hours, and then stir it at room temperature for 15 minutes. Repeat this process. After 3 days, a silk fiber mixture that has not been completely dissolved is obtained.
[0054] A4. The obtained solution was placed in a dialysis bag (MWCO=10000 kDa) and dialyzed in deionized water for 2 days to remove salt ions in the mixture. The mixture was ultrasonicated in an ice bath for 20 minutes, then centrifuged at 6000 rpm for 15 minutes, and the supernatant was retained. The dialyzed solution was ultrasonically centrifuged, and the supernatant was precooled at -20°C, then placed in a freeze dryer and freeze-dried for 60 hours to obtain white powder SNF, which was stored in a 4°C refrigerator.
[0055] Preparation of GO / SNF multilayer membrane, schematic diagram Figure 2 As shown, the steps are:
[0056] A5. Substrate treatment: Cut the silicon wafer into rectangular samples with a width of 1 cm, place them in anhydrous ethanol for ultrasonic cleaning for 10 minutes, then rinse them with ultrapure water for 3 times, and blow dry them with a nitrogen blower. Use a plasma cleaner to clean the silicon wafer and the glass slide, making the silicon wafer surface hydrophilic and negatively charged.
[0057] A6. Immerse the silicon wafer in a GO solution with a concentration of 1 mg / mL for 15 minutes, and wash it three times with deionized water, with the washing time being 2 minutes, 1 minute, and 1 minute respectively. Then immerse the silicon wafer in a SNF solution with a concentration of 1 mg / mL for 15 minutes, and also go through three washing steps to form a double layer. According to the number of layers required, the above materials are subjected to the same soaking and rinsing procedures, and the assembly process is repeated to finally obtain a (GO / CHI)n (n represents the number of double layers) multilayer film structure.
[0058] A7, chemical crosslinking: The multilayer film was immersed in a 0.05M morpholineethanesulfonic acid (MES) solution containing 0.2M EDC and 5MM NHS for 10 minutes. Then, the crosslinked multilayer film was immersed in a 1×PBS buffer for 10 minutes to clean the residual solution. After that, it was immersed in a 2.5% glutaraldehyde solution for 40 minutes for the second crosslinking. Finally, it was rinsed three times with ultrapure water to remove the residual glutaraldehyde, and the multilayer film was dried with nitrogen.
[0059] Example 2: Characterization by Scanning Electron Microscope (SEM)
[0060] UV-VIS was used to observe the thickness change of the coating during the layer-by-layer self-assembly process of the substrate, with a wavelength scanning range of 190-900 nm and a scanning rate of 2 nm.
[0061] The surface morphology of GO / SNF multilayers was studied by SEM. (SNR) was successfully prepared on a silicon wafer substrate 10 、(GO / SNF) 10 、(GO / SNF) 20 ( Figure 3 ), it can be seen from the figure that the multilayer membranes with different numbers of layers all show highly rough and porous surface structures. The increase in the number of layers makes the membrane surface more rough and irregular, and the intricate fiber structure forms many tiny holes. This porous structure is the key to the adsorption of drugs by multilayer membranes.
[0062] Embodiment 3:
[0063] Evaluation of drug loading of DOX-(GO / SNF)
[0064] Schematic diagram of (GO / SNR)n multilayer film loaded with DOX drug Figure 4 As shown, the substrate formed with the graphene oxide / silk fibroin nanofiber multilayer film is immersed in a drug solution for 1.0h, and then the multilayer film is washed to remove the unloaded drug, thereby obtaining the graphene oxide / silk fibroin nanofiber drug-loaded multilayer film. The graphene oxide / silk fibroin nanofiber drug-loaded multilayer film is attached to the substrate, and the graphene oxide / silk fibroin nanofiber drug-loaded multilayer film can be peeled off from the substrate.
[0065] Weigh 25 mg of doxorubicin DOX into a 25 mL volumetric flask, dissolve it with ultrasound, and dilute it to the mark with deionized water to prepare the stock solution. Accurately measure 1.5 mL of the stock solution into a 50 mL volumetric flask, use a solution without doxorubicin as a blank control, perform full wavelength scanning with UV-vis, and select 314 nm as the absorbance detection peak of DOX. Figure 5As shown, the absorbance of (GO / SNF)n (n = 0, 4, 8, 12, 16, 20) multilayers gradually increases with the assembly of every four layers. In addition, the absorbance of CHI / SNF multilayers increases linearly with the number of layers, indicating that the drug loading of (GO / SNF) is uniform and increases linearly with the increase of the thickness of the multilayer.
[0066] Example 4: GO / SNF multilayer film for DOX loading and in vitro release
[0067] The multilayer film was immersed in a 1 mg / mL standard solution for 1 h, and then the multilayer film was washed with deionized water to remove the unloaded drug to obtain a drug-loaded multilayer film. The DOX-GO / SNF multilayer film was immersed in a release medium of 10 mL 1× PBS buffer and incubated at 37°C. Multiple time points (0-540 min) were set, and 1 mL of PBS buffer containing DOX was collected at each time point (1 ml of fresh PBS was added to the release medium at the same time). The in vitro cumulative release experiment of DOX was measured by UV-vis.
[0068] The silk protein nanofibers that retain the fibril structure make the GO / SNF multilayer membrane have a porous structure. Doxorubicin DOX, as a small molecule drug, is loaded into the multilayer membrane by physical adsorption. This physical method of loading drugs is more advantageous than chemical methods in principle because it does not require the formation of covalent bonds, and the loading and release of drugs are reversible. The DOX-GO / SNF multilayer membrane was placed in a PBS buffer with the same osmotic pressure and temperature as the human body to analyze the drug release characteristics. Figure 6 The results of the study on drug release behavior of GO / SNF multilayer films are shown in Figure 2. Figure 6 It can be seen that DOX drug is released in PBS by diffusion. As the number of GO / SNF multilayers increases, the drug loading also increases. However, the drug release curves of GO / SNF multilayers with different drug loading contents are basically the same, which shows that GO / SNF multilayers have a rapid drug release phenomenon. In addition, Figure 6 Medium, pure (SNF) 10 、(GO / SNF) 10 and (GO / SNF) 20 The drug loading of the multilayer films was 0.45±0.09μg / cm 2 , 0.62±0.45μg / cm 2 and 1.02±0.10μg / cm 2 Under the same number of layers, (GO / SNF) 10 Drug loading is (SNF) 10 1.38 times of that under different film conditions, (GO / SNF) 20 Drug loading is (GO / SNF) 10This indicates that compared with pure (SNF) 10 Membrane, (GO / SNF) 10 The drug loading of the composite membrane increased significantly, which is consistent with Figure 7 The SEM microstructure of the multilayer film after drug release is consistent with that of the (SNF) 10 The surface structure is dense and compact, (GO / SNF) 10 The porous structure on the surface of the composite membrane can effectively increase the loading amount of small drug molecules. Secondly, the drug loading capacity can also be effectively improved by increasing the number of layers of the multilayer membrane. Therefore, the drug loading capacity can be regulated by changing the number of layers of the (GO / SNF)n multilayer membrane.
[0069] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a graphene oxide / silk fibroin nanofiber multilayer film, characterized in that: The following steps are involved: S1, immersing the substrate in a graphene oxide solution and then washing with deionized water; S2, immersing the substrate obtained in step S1 into the silk fibroin nanofiber solution, and then washing with deionized water to form a GO / SNF double-layer membrane on the substrate; S3, repeating the immersion and cleaning operations in steps S1 and S2 on the substrate containing the GO / SNF double-layer film obtained in S2 to form a (GO / SNF)n multilayer film on the substrate, wherein n represents the number of GO / SNF layers; S4. The (GO / SNF)n multilayer film obtained in S3 is cross-linked to form a cross-linked (GO / SNF)n multilayer film on the substrate, that is, a graphene oxide / silk fibroin nanofiber multilayer film.
2. The method for preparing a graphene oxide / silk fibroin nanofiber multilayer film according to claim 1, characterized in that: In step S1, before immersing the substrate in the graphene oxide solution, the substrate is cleaned using a plasma cleaning apparatus so that the substrate is negatively charged.
3. The method for preparing a graphene oxide / silk fibroin nanofiber multilayer film according to claim 1, characterized in that: In step S1, the concentration of the graphene oxide solution is 1.0-1.5 mg / mL; In step S2, the concentration of the silk fibroin nanofiber solution is 1.0-1.5 mg / mL.
4. The method for preparing a graphene oxide / silk fibroin nanofiber multilayer film according to claim 1, characterized in that: In step S2, the silk fibroin nanofiber (SNF) is prepared by the following method: A1. Put the chopped silk cocoons into a degumming solution, boil them, wash them, and dry them to obtain degummed silk; A2, dissolving the degummed silk in a sodium hydroxide / urea mixed solution, freezing it first, then stirring it, and repeating the operation to obtain a silk fibroin fiber solution; A3, putting the silk fibroin fiber solution into a dialysis bag, placing it in deionized water, dialyzing, ultrasonically centrifuging the dialyzed solution, taking the supernatant for precooling, and then freeze-drying it in a freeze dryer to obtain white powder silk fibroin nanofibers; In the step A1, the degumming solution is a 0.4-0.6% (w / v) sodium carbonate or sodium bicarbonate aqueous solution. In step A2, in the sodium hydroxide / urea mixed solution, the mass ratio of sodium hydroxide to urea is 1.0-1.5:
1.
5. The method for preparing a graphene oxide / silk fibroin nanofiber multilayer film according to claim 1, characterized in that: In step S4, the method for cross-linking treatment is: The substrate formed with the (GO / SNF)n multilayer film structure is immersed in a 0.05-0.06 mol / L morpholineethanesulfonic acid solution containing 0.2-0.3 mol / L 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 5.0-6.0 mmol / L N-hydroxysuccinimide for 20-30 min, and then cross-linked in a 2.5% glutaraldehyde solution for 30-60 min, and rinsed with deionized water to form a cross-linked (GO / SNF)n multilayer film on the substrate, that is, a graphene oxide / silk fibroin nanofiber multilayer film.
6. A graphene oxide / silk fibroin nanofiber multilayer membrane prepared by the preparation method according to any one of claims 1 to 5.
7. Use of a graphene oxide / silk fibroin nanofiber multilayer membrane prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The graphene oxide / silk fibroin nanofiber multilayer film is used for drug loading to prepare the graphene oxide / silk fibroin nanofiber drug loading multilayer film.
8. A method for preparing a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film, characterized in that: The following steps are involved: The substrate formed with the graphene oxide / silk fibroin nanofiber multilayer film is immersed in a drug solution for 1.0-1.5 hours, and then the multilayer film is washed to remove unloaded drugs, thereby obtaining a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film; The substrate on which the graphene oxide / silk fibroin nanofiber multilayer film is formed is prepared by any one of claims 1-5.
9. The method for preparing a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film according to claim 8, characterized in that: The concentration of the drug solution is 1.0-1.5 mg / mL.
10. The method for preparing a graphene oxide / silk fibroin nanofiber drug-loaded multilayer film according to claim 8, characterized in that: The drug is doxorubicin used for anti-tumor.